Muscle synergies in archery: an explorative study on experienced athletes with and without physical disability - Vendrame, E.; Rum, L.; Belluscio, V.; Truppa, L.; Vannozzi, G.; Lazich, A.; Bergamini, E.; Mannini, A. (43rd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), Mexico 2021, 2021)
Archery technique requires a coordinated activation of shoulder girdle and upper extremity muscles to perform a successful shot. The analysis of muscle synergies can provide information about the motor strategy that underlies the shooting performance, also supporting the investigation of motor impairments in athletes with disability. For this purpose, electromyographic (EMG) data from five muscles were collected from a non-disabled and a W1 category Paralympic athlete, and muscle synergies were extracted from EMG envelopes using non-negative matrix factorization. Muscle synergies analysis revealed features of the motor strategy specific to the athletes` shooting technique, such as the contribution of the biceps muscle instead of the posterior deltoid during the arrow drawing and target aiming in the Paralympic athlete compared to the non-disabled athlete. It is concluded that the evaluation of the muscle synergies may be a valuable tool for exploring the motor strategies adopted by athletes with disability, providing useful information to improve athletic performance and possibly prevent the risk of injury.